THE NECROTIC-APOPTOTIC CHANGES IN BLOOD MONONUCLEAR PHAGOCYTES IN THE EXPERIMENTAL BACTERIAL-IMMUNE PERIODONTITIS DEVELOPMENT - Demkovych, A.Ye. (World of Medicine and Biology, 2018)
Mechanisms of the inflammatory process development in the periodontal complex include a number of complicated processes leading to the generalization and chronicization, tooth loss and the occurrence of complications in the other organs. The purpose of the study was to determine the level of apoptotic changed and necrotic mononuclear blood phagocytes in the dynamics of development of experimental bacterial-immune periodontitis. The paper presents the results of studies of early and late apoptosis indices of blood monocytes on the 7th and 30th days of the development of the inflammatory process in periodontal tissues. Monocytes were isolated from blood of experimental animals by gradient centrifugation. Evaluation of necrosis and apoptosis of mononuclear phagocytes was carried out by the flow laser cytofluorimetry. The results were statistically processed using parametric and nonparametric statistical methods. Dynamics of dead cells number was revealed during the formation of the focus of inflammation in the periodontal complex. In particular, the progress of experimental periodontitis was accompanied by the increase of annexin-positive (early apoptosis) and necrotic monocytes content, which is associated with increased intensity of their formation in response to antigen stimulation. In the simulated pathology the induced cell death was achieved mainly by apoptosis.
Keywords: Bacterial-immune periodontitis; inflammation; mononuclear phagocytes; necrosis; apoptosis